Dynamic Change in Mean Platelet Volume and Delayed Cerebral Ischemia After Aneurysmal Subarachnoid Hemorrhage - Chen, Liuwei; Zhang, Quanbin (Frontiers in Neurology, 2020)
Abstract Background: The mean platelet volume (MPV) has been shown to predict short-term outcomes in patients who have experienced aneurysmal subarachnoid hemorrhage (aSAH). The purpose of this study was to explore the temporal variation of MPV in patients with aSAH and its relationship to the development of delayed cerebral ischemia (DCI). Methods: Data from 197 consecutive aSAH patients who were treated at our institution between January 2017 and December 2019 were collected and analyzed. Blood samples to assess MPV were obtained at 1-3, 3-5, 5-7, and 7-9 d after the initial hemorrhage. Univariate and multivariate analyses were performed to investigate whether MPV was an independent predictor of DCI and the receiver operating characteristic (ROC) curve and area under the curve (AUC) were determined. Results: The MPV values in patients with DCI were significantly higher compared to those without DCI at 1-3, 3-5, 5-7, and 7-9 d after hemorrhage (P < 0.001). The trend for MPV in patients with DCI was increased at first and then decreased. The transition from increases to decreases occurred at 3-5 d after hemorrhage. The optimal cutoff value for MPV to accurately predict DCI was 10.35 fL at 3-5 d after aSAH in our cohort. Furthermore, the MPV observed at 3-5 d was an independent risk factor for DCI (odds ratio, [OR] = 4.508, 95% confidence interval [CI]: 2.665-7.626, P<0.001). Conclusions: MPV is a dynamic variable that occurs during aSAH, and the early rise in MPV is associated with the development of DCI.